Prestress and strength of the threaded joints M16 under low cyclic bending/Srieginių jungčių M16 įveržimas ir atsparumas mažacikliam lenkimui - Krenevičius, Algimantas; Leonavičius, Mindaugas (Journal of Civil Engineering and Management, 1998)
The article provides experimental data of fracture resistance of threaded joints under low cycle bending. The tests have been carried out at normal and higher temperatures up to 320°C. Experimental examinations have shown that in some cases total of stretching and bending stress reach a plastic range and penetrate to a certain depth. A further repeated load has an influence on the strength and liability of connections. Decomposition, associated with the process of inelastic deformation, can be local or general one. The inelastic deformations cause in the threaded joints progressive geometrical changes, redistribution of stretching efforts and decreasing of prestress. By slackening the stretch of jointing elements the leak-proofness can be broken in the process of cyclic deformation. Experimental studies have shown that the appearance and propagation of cracks have specific features which are characteristic only of threaded joints. It may be one-sided or two-sided crack caused by the acting of stretching force an variable bending moment of symmetric cycle. The investigation of threaded joint loosening mechanisms shows that this process depends of the prestress and crack propagation. When static and cyclic stress acquires definite values and relations, loss of stability of the axial dimensions of the joints as well as the decrease of the prestress can be observed.Article in Lithuanian.First Published Online: 26 Jul 2012